2020
DOI: 10.1097/01.naj.0000660020.17156.ae
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: An Investigation of Career Choice Regret Among American Nurses

Abstract: Purpose: To explore whether burnout is an independent predictor of career choice regret among nurses. Methods: In November 2017 we invited a random sample of 89,995 members of the American Nurses Association to participate in an anonymous online survey. The survey collected demographic and professional information and included the Maslach Burnout Inventory–Human Services Survey for Medical Personnel (known as the MBI-HSS [MP]), as well as several items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…However, excessive sleep duration can also cause psychological problems ( 50 52 ), affecting the efficiency of postgraduates' work and study, thereby reducing their career identity. Our findings also indicate that consistent with a previous study ( 53 ), dental postgraduates with job burnout are more likely to experience career choice regret.…”
Section: Discussionsupporting
confidence: 92%
“…However, excessive sleep duration can also cause psychological problems ( 50 52 ), affecting the efficiency of postgraduates' work and study, thereby reducing their career identity. Our findings also indicate that consistent with a previous study ( 53 ), dental postgraduates with job burnout are more likely to experience career choice regret.…”
Section: Discussionsupporting
confidence: 92%
“…Existing studies have found that age, gender and tenure can affect employee thriving and career attitudes (e.g. Chung, 2002 ; Dyrbye et al, 2002 ; Jiang, 2017 ; Jiang et al, 2021 ). As a result, these three variables are included as control variables in all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Fears of personal safety and fears of infecting loved ones were prevalent in responses, which can lead to career choice regret and nurse burnout. 20 …”
Section: Discussionmentioning
confidence: 99%